Implementasi Teori Belajar Konstruktivistik Jerome Bruner dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 9 Yogyakarta - Wibisono Yudhi Kurniawan (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
The effectiveness of implementation Islamic course depends on the approach that is used, moreover the constructivist learning theory can help teachers to solve learning problems. Research method that is used is observation, interview, and documentation. The aims of the research are (1) to get to know the implementation of Jerome Bruner learning theory in Islamic course. (2) To examine the supporting aspects and inhibition in the implementation of Jerome Bruner learning theory (3) To discover the problem solution in the implementation of Jerome Bruner learning theory in Islamic course. Based on the data analysis, the conclusion are: (1) the implementation of Jerome Bruner learning theory in Islamic course to create fun learning for students, and its implementation in Islamic course in VII grade of Junior High School 9 Yogyakarta has applied effectively based on the principal and the learning procedure. (2) In the implementation of Jerome Bruner learning theory has run well, hence completed with the supporting factors and inhibition factors. (3) The problem solving of Jerome Bruner learning method in Islamic course are teaching some characters in students such as self-confidence and tolerance the improvement of teachers quality through training participation, workshop, etc. also improving the students learning motivation.